AKIBAT HUKUM BAGI PEMEGANG HAK BEKAS EIGENDOM VERPONDING DALAM SENGKETA KEPEMILIKAN TANAH - Pedro Sutanto (Jurnal Dialektika Hukum, 2022)
Eigendom verponding is a right to land ownership whose rights must beadjusted through the conversion provisions of the UUPA. The implementation of theconversion was given a period of time until September 24, 1980. In practice, therewas still recognition of ownership of the formerland eigendom verponding whichlater resulted in a dispute over the land. For example, the acknowledgment ofownership of the former eigendom verponding in decision number19/Pdt.G/2019/PN.Slw and decision number 30/Pdt.G/2019/PN.Unr. Theformulation of the problem in the research: 1. What is the legal status of theformerland eigendom verponding which has not been converted according to thelaws and regulations? 2. What are the legal consequences for holders of ex-rightseigendom verponding that are not converted in land ownership disputes?The approach method used is qualitative with the type of normative legalresearch. The main data source comes from secondary data which is alsointerviewed as supporting data. Secondary data sources are divided into primarylegal materials, secondary legal materials, and tertiary legal materials. Datacollection techniques using library research and field studies in the form ofinterviews.